The Effect of Aerobic Activity on Blood Sugar In BKMF Volleyball FIKK UNM Athletes - wahyudin, Wahyudin; Ilyas, Muslim Bin; Mappanyukki, Atssam (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of aerobic activity on the increase in blood sugar in BKMF Volleyball FIKK UNM athletes. The research method uses a statistical test with the application of SPSS 21. The research sample consisted of 20 athletes whose blood sugar levels were tested before and after doing aerobic activities. The results of the analysis showed that the average blood sugar level before aerobic activity (pre-test) was 93.1500, while after aerobic activity (post-test) decreased to 82.8500. Statistical tests showed a significance value (sig. 2-tailed) of 0.000 (p<0.05), which indicated a significant difference between blood sugar levels before and after aerobic activity. The average difference in blood sugar levels between the initial test and the final test was 10.3, which showed the influence of aerobic activity on the decrease in blood sugar levels in BKMF Volleyball FIKK UNM athletes. Thus, it can be concluded that aerobic activity contributes to lowering blood sugar levels in volleyball athletes.